O perfil sociodemográfico e criminal dos reincidentes no sistema de justiça criminal do Amazonas - Abensur, Elieder Bonet (2018)
In recent years, Brazil has witnessed a considerable increase in rates of criminal recidivism, becoming a phenomenon of great relevance, gaining prominence in the most varied public and academic debates that involve issues such as public security, criminal justice system and penitentiary system. The data from the last IPEA report in 2015 point to certain social vulnerabilities of this population and open space for analysis of the local reality. Based on these premises, it is proposed to analyze the sociodemographic and criminal profiles of recidivists in the state of Amazonas, based on information collected from the Criminal Justice System, performing statistical treatment in the data with inferential and descriptive analysis, estimating and identifying the main aspects of the sociodemographic and históricocriminalof the prisoners who had filed criminal proceedings in 2016 with new convictions in 2017. A discussion of the legal, doctrinal, criminological and legal concepts of criminal recidivism in the literature was also promoted, demonstrating the causal / explanatory relations of the phenomenon studied. The general context of the analyzed variables allowed us to infer that the criminal recidivism of Amazonas has peculiar characteristics that distinguish them from other profiles already studied in the country, whose differences are explained during the course of the work, allowing a fluid and stimulating reading of the theme.